Pembuatan Referensi Praktik Dasar Perancangan Progressive Die pada Perangkat Lunak Siemens NX - Suseno, Ignatius; Sutopo, Antonius Adi; Rizaldi S, Fajar (Politeknik Negeri Padang, 2025)
As a continuous improvement through state-of-the-art discovery and uniqueness for the learning material of the Progressive Die Design practical lecture, it is necessary to update it by reviewing 2 aspects, namely